Analisis Dan Perancangan Aplikasi Opname Audit Aset Non-Unit Berbasis Mobile Apps - Yulmansyah Rizky Rahman; Lutfi Harris (PT. Hasba Edukasi Mandiri, 2025)
This paper aims to analyze and design a new application to improve the non-unit asset opname audit procedure within PT XYZ’s Internal Audit Division. The application, developed using AppSheet (a low-code development platform), streamlines the traditional audit method, which involves multiple time-consuming steps. By employing the SDLC (classical waterfall) methodology, the new application simplifies and automates various stages of the process, resulting in a more efficient and user-friendly workflow. The application design enhances the workflow of the audit procedure by eliminating steps that does not have significant added value.